Analisis Sifat Termal Dan Kuat Impak Green-Sandwich Composite Berdasarkan Variasi Susunan Lapisan (Stacking Sequence) - Isep Abdul Rojak; Ilham Ary Wahyudie; Juanda Juanda (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
The use of environmentally friendly composite materials has been increasingly developed as an alternative to conventional materials for automotive components. This study aimed to investigate the effect of stacking sequence variations on the thermal insulation performance and impact strength of Green Sandwich Composites reinforced with coconut coir fiber, woven fiberglass, a balsa wood core, and polyester resin. The specimens were fabricated using the hand lay-up method combined with vacuum bagging, followed by thermal insulation and Charpy impact testing. The data were analyzed using One-Way ANOVA. The results showed that the GF–NF–C–NF–GF configuration exhibited the best performance, achieving a thermal insulation efficiency of 40.65% and an impact strength of 198.98 kJ/m². However, the One-Way ANOVA results indicated that stacking sequence variations had no statistically significant effect on either parameter at a 5% significance level. Nevertheless, the GF–NF–C–NF–GF configuration is recommended as the optimum stacking sequence because it provides the best combination of thermal and mechanical performance for environmentally friendly automotive bumper applications.